Integration of LMS platform and open source algorithm for detection and prevention of plagiarism in Higher Education - Reducindo, Isnardo; Rivera, Luis R.; Rivera, Julio; Olvera, Miguel A. (Revista General de Información y Documentación, 2017)
The work shows the results of the first phase of a research project, aimed at addressing from a new perspective the problem of plagiarism in the digital era and as part of the processes of academic training, which is pursued through the integration of technological tools . It is an application for plagiarism detection built from two open source applications, a platform for distance education and an adaptive plagiarism detection algorithm. The methodology for the development, integration and implementation of the aforementioned tool is also presented in general terms, as well as the analysis of statistical data from a sample of students at the higher level of the Faculty of Information Sciences (FCI) of the Autonomous University of San Luis Potosí (UASLP), Mexico. The initial analysis yields data of interest and probabilistic models as a first approach to the problem, which will be analyzed from an academic focus, in such a way as to identify the degree of participation of students in this type of practice as part of their university education.